Addressing Instability Issues in Microgrids Caused By Constant Power Loads Using Energy Storage Systems - (:unkn) unknown (My University, 2016)
Renewable energy sources, the most reasonable fuel-shift taken over the naturally limited conventional fuels, necessarily deal with the self-functional microgrid system rather than the traditional grid distribution system. The study shows that the microgrid system, a comparatively low-powered system, experiences the challenge of instability due to the constant power load (CPL) from many electronic devices such as inverter-based systems. In this dissertation, as a methodical approach to mitigate the instability complication, AC microgrid stability is thoroughly investigated for each and every considerable parameter of the system. Furthermore, a specific loading limit is depicted by evaluating the stability margin from the small signal analysis of the microgrid scheme. After demonstrating all cases regarding the instability problem, the storage-based virtual impedance power compensation method is introduced to restore the system stability and literally extend the loading limit of the microgrid system. Here, a PID controller is implemented to maintain the constant terminal voltage of CPL via current injection method from storage. Since the system is highly nonlinear by nature, advanced nonlinear control techniques, such as Sliding Mode Control and Lyapunov Redesign Control technique, are implemented to control the entire nonlinear system. Robustness, noise rejection, and frequency variation are scrutinized rigorously in a virtual platform such as Matlab/Simulink with appreciable aftermaths. After that, a comparative analysis is presented between SMC and LRC controller robustness by varying CPL power. From this analysis, it is evident that Lyapunov redesign controller performs better than the previous one in retaining microgrid stability for dense CPL-loaded conditions. Finally, to ensure a robust storage system, Hybrid Energy Storage System is introduced and its advantages are discussed as extended research work.
Keywords: Constant Power Load; Hybrid Energy Storage System; Lyapunov Redesign Control; Micorgird; Sliding Mode Control; Stability Improvement